Lithium-sulfur battery positive electrode material, preparation method thereof and lithium-sulfur battery

By mixing materials such as molybdenum powder to form a positive electrode active liquid and applying it to the battery separator, the problem of lithium polysulfide shuttle effect in lithium sulfur batteries is solved, the conductivity and flexibility are improved, and swelling and short circuit are suppressed.

CN119581500APending Publication Date: 2025-03-07HUANENG SUIXIAN JIESHAN WIND POWER CO LTD +1

Patent Information

Application Number
CN202411635665.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The shuttle effect of lithium polysulfide in lithium-sulfur batteries leads to rapid attenuation of battery capacity, and existing intercalation materials have problems such as decreased conductivity, swelling and short circuit.

Method used

Molybdenum powder, sulfur powder, conductive agent, binder and organic solvent are mixed in proportion to form a positive electrode active liquid, and coated on the battery separator to obtain the lithium-sulfur battery positive electrode material through solid phase conversion and vacuum drying.

Benefits of technology

The conductive properties of the lithium-sulfur battery positive electrode material is improved, the shuttle effect of polysulfide is suppressed, the swelling of the positive electrode active coating is prevented, and the overall flexibility is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581500A_ABST
    Figure CN119581500A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium-sulfur batteries, in particular to a lithium-sulfur battery positive electrode material, a preparation method of the lithium-sulfur battery positive electrode material and a lithium-sulfur battery, and the preparation method of the lithium-sulfur battery positive electrode material comprises the following steps: S1, mixing molybdenum powder, sulfur powder, a conductive agent, a binder and an organic solvent in proportion to obtain a positive electrode active solution; and S2, coating a battery diaphragm with the positive electrode active liquid in the step S1, and drying to obtain the lithium-sulfur battery positive electrode material. In the application, the catalyst molybdenum has excellent binding capacity and conversion capacity to polysulfide, the conductivity of the positive electrode material of the lithium-sulfur battery is improved, and the positive electrode active coating and the battery diaphragm are integrally formed, so that the positive electrode active coating can be prevented from swelling when encountering electrolyte, the shuttle effect of the polysulfide of the lithium-sulfur battery is inhibited, and the service life of the lithium-sulfur battery is prolonged. And the overall flexibility of the lithium-sulfur battery positive electrode material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-sulfur batteries, and in particular to a lithium-sulfur battery positive electrode material and a preparation method thereof, and a lithium-sulfur battery. Background Art

[0002] Lithium-sulfur battery is a lithium battery with metallic lithium as the negative electrode and elemental sulfur or organic sulfide as the positive electrode. On the one hand, the theoretical energy density of lithium-sulfur battery is 7 to 8 times that of current lithium-ion battery. On the other hand, lithium-sulfur battery using sulfur as the positive electrode material is the solid-state positive electrode material with the highest known theoretical specific capacity used in lithium-sulfur batteries. In addition, elemental sulfur also has the characteristics of abundant reserves in nature, low price, and environmental friendliness. Therefore, lithium-sulfur batteries have gradually become the research focus and hotspot of the new generation of clean energy storage devices.

[0003] During the charge and discharge process, the intermediate product lithium polysulfide produced by the lithium-sulfur battery can dissolve in the electrolyte and shuttle back and forth between the positive and negative electrodes, causing the battery capacity to decay rapidly. This process is called the shuttle effect. By adding an intercalation material between the positive electrode and the PP separator, lithium polysulfide can be prevented from diffusing to the negative electrode, thereby inhibiting the lithium polysulfide shuttle effect. However, there are still several problems: (1) The intercalation material contains a catalyst, which is insulating in itself, such as iron oxide, which is not conducive to forming a continuous conductive path; (2) The intercalation material is based on organic matter, such as polyvinylidene fluoride, which swells when in contact with the electrolyte and easily bypasses the PP separator to contact the negative electrode and cause a short circuit; (3) The intercalation material contains an insulating polymer, such as polyvinylidene fluoride, which causes the overall conductivity of the lithium-sulfur battery to decrease.

[0004] In view of this, this application is specially filed. Summary of the invention

[0005] The present application provides a lithium-sulfur battery positive electrode material to solve the problem of polysulfide shuttle effect in lithium-sulfur batteries, while simplifying the process and increasing the flexibility of the material.

[0006] On the one hand, the present application provides a method for preparing a positive electrode material for a lithium-sulfur battery, comprising the following steps:

[0007] Step S1: mixing molybdenum powder, sulfur powder, conductive agent, binder and organic solvent in proportion to obtain a positive electrode active solution;

[0008] Step S2: coating the positive electrode active solution in step S1 on the battery separator, and obtaining the positive electrode material of the lithium-sulfur battery after drying.

[0009] In some embodiments, step S2 specifically includes:

[0010] Step S21: laying a battery separator on a glass plate, coating the positive electrode active solution in step S1 on the battery separator, and then immersing it in water to perform a solid phase conversion of the positive electrode active coating;

[0011] Step S22: Separate the battery separator with the positive electrode active coating formed in step S21 from the glass plate, dry it at room temperature for 12 hours, and then vacuum dry it for 12 hours to obtain a lithium-sulfur battery positive electrode material, wherein the vacuum drying temperature is 40°C to 80°C.

[0012] In some embodiments, in step S22, the solid-phase conversion temperature is 20° C. to 50° C., and the solid-phase conversion time is 4 h to 12 h.

[0013] In some embodiments, in step S2, the battery separator is a polyethylene, polypropylene or polyimide separator.

[0014] In some embodiments, the step S1 specifically includes:

[0015] Step S11: Grind the molybdenum powder, sulfur powder and conductive agent, add an organic solvent to dissolve them, and after they are fully dissolved, add a binder and mix to form a suspension.

[0016] Step S12: The suspension in step S11 is subjected to an oil bath to obtain a positive electrode active solution.

[0017] In some of the embodiments, in step S11, the mass ratio of molybdenum powder, sulfur powder, conductive agent, binder and organic solvent is 1:10:10:5-15:100.

[0018] In some of the embodiments, in step S11, the conductive agent is one or more of carbon nanotubes and Ketjen black, the binder is polyvinylidene fluoride, and the organic solvent is N,N-dimethylformamide.

[0019] In some embodiments, in step S12, the oil bath temperature is 60° C., the oil bath time is 6 h to 12 h, and the stirring speed is 100 rpm to 400 rpm.

[0020] On the other hand, the present application also provides a lithium-sulfur battery positive electrode material prepared by any of the above-mentioned preparation methods.

[0021] On the other hand, the present application also provides a lithium-sulfur battery, comprising a negative electrode material, a positive electrode material and an electrolyte, wherein the positive electrode material is a lithium-sulfur battery positive electrode material prepared by any of the above-mentioned preparation methods or is the above-mentioned lithium-sulfur battery positive electrode material.

[0022] After adopting the above technical solution, the present application has the following beneficial effects compared with the prior art.

[0023] 1. The preparation method of the positive electrode material of a lithium-sulfur battery in the present application utilizes a catalyst molybdenum to replace the catalyst iron oxide. The catalyst molybdenum not only has excellent electrical conductivity, but also has excellent binding and conversion capabilities for polysulfides, thereby improving the electrical conductivity of the positive electrode material of a lithium-sulfur battery.

[0024] 2. In the preparation method of the positive electrode material of the lithium-sulfur battery in the present application, the positive electrode active coating and the battery separator are integrally formed, which can not only prevent the positive electrode active coating from swelling when encountering the electrolyte, inhibit the polysulfide shuttle effect of the lithium-sulfur battery, but also improve the overall flexibility of the positive electrode material of the lithium-sulfur battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a flow chart of the method for preparing the positive electrode material of the lithium-sulfur battery in this application.

[0026] Figure 2 It is a logic block diagram of the preparation method of the positive electrode material of the lithium-sulfur battery in this application.

[0027] Figure 3 This is a comparison diagram of the circular electrode sheets of Comparative Example 1 and Example 1 before and after the swelling test;

[0028] Figure 3 (a) and (b) are schematic diagrams of the Mo / C-CNT@PVDF circular electrode sheet before and after encountering the electrolyte; Figure 3 (c) and (d) are schematic diagrams of the Mo / C-CNT@PVDF / / PP circular electrode sheet before and after encountering the electrolyte.

[0029] Figure 4 This is a schematic diagram of the tensile test results of the lithium-sulfur battery positive electrode materials in Example 1 and Comparative Examples 1 and 2.

[0030] Figure 5 This is a schematic diagram of the X-ray diffraction test results of the positive electrode active coating Mo / C-CNT@PVDF in Example 1 and the positive electrode active coating C-CNT@PVDF in Comparative Example 2.

[0031] Figure 6 This is the XPS spectrum of the lithium-sulfur battery positive electrode material before and after the charge and discharge cycle in Example 1;

[0032] Figure 6 (a) is the XPS spectrum of Li 1s; Figure 6 (b) is the XPS spectrum of F1s orbital; Figure 6 (c) is the XPS spectrum of Mo element. DETAILED DESCRIPTION

[0033] The technical solution of the present application will be described clearly and completely below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0034] First, as Figure 1 As shown, the present application embodiment provides a method for preparing a positive electrode material for a lithium-sulfur battery, comprising the following steps:

[0035] Step S1: mixing molybdenum powder, sulfur powder, conductive agent, binder and organic solvent in proportion to obtain a positive electrode active solution;

[0036] Step S2: coating the positive electrode active solution in step S1 on the battery separator, and obtaining the positive electrode material of the lithium-sulfur battery after drying.

[0037] According to the preparation method of the positive electrode material of a lithium-sulfur battery of the present application, a catalyst molybdenum is used to replace the catalyst iron oxide. The catalyst molybdenum not only has excellent electrical conductivity, but also has excellent binding ability and conversion ability for polysulfides, thereby improving the electrical conductivity of the positive electrode material of the lithium-sulfur battery. The positive electrode active coating and the battery separator are integrally formed, which can not only prevent the positive electrode active coating from swelling when encountering an electrolyte, inhibit the polysulfide shuttle effect of the lithium-sulfur battery, but also improve the overall flexibility of the positive electrode material of the lithium-sulfur battery.

[0038] like Figure 2 As shown, in this embodiment, step S2 specifically includes:

[0039] Step S21: laying a battery separator on a glass plate, coating the positive electrode active solution in step S1 on the battery separator, and then immersing it in water to perform a solid phase conversion of the positive electrode active coating;

[0040] Step S22: Separate the battery separator with the positive electrode active coating formed in step S21 from the glass plate, dry it at room temperature for 12 hours, and then vacuum dry it for 12 hours to obtain a lithium-sulfur battery positive electrode material, wherein the vacuum drying temperature is 40°C to 80°C.

[0041] In this embodiment, the positive electrode active coating is solid-phase transformed so that the positive electrode active coating and the battery separator are tightly bonded, and then the integrally formed positive electrode active coating and the battery separator are dried to ensure the stability of the positive electrode material of the lithium-sulfur battery.

[0042] In this embodiment, in the step S21, the positive electrode active liquid in the step S1 is coated on the battery separator to form a positive electrode active liquid film with a thickness of 100um to 300um, so as to prevent the positive electrode material of the lithium-sulfur battery obtained after drying from being too thin or too thick, thereby affecting the conductive performance of the lithium-sulfur battery or the cycle stability and safety of the lithium-sulfur battery.

[0043] In the present embodiment, in the step S22, the solid phase conversion temperature is 20°C to 50°C, and the solid phase conversion time is 4h to 12h, so that the positive electrode active coating and the battery separator are integrally formed, which not only limits the swelling problem of the positive electrode active coating when encountering the electrolyte, but also greatly reduces the interface resistance between the positive electrode active coating and the battery separator. At the same time, the integrally formed positive electrode active coating and the battery separator have higher flexibility as a whole.

[0044] The battery separator is a thin film used to separate the positive and negative electrodes during the electrolysis reaction to prevent the loss of energy by direct reaction in the electrolyte, which directly affects the battery's capacity, cycle, safety performance and other characteristics. In this embodiment, in step S2, the battery separator is polyethylene (PP), polypropylene (PE) or polyimide separator (PI), which has a wide range of raw materials, low cost, and a simple and controllable process, which is conducive to large-scale implementation.

[0045] like Figure 2 As shown, in this embodiment, step S1 specifically includes:

[0046] Step S11: Grind the molybdenum powder, sulfur powder and conductive agent, add an organic solvent to dissolve them, and after they are fully dissolved, add a binder and mix to form a suspension.

[0047] Step S12: The suspension in step S11 is subjected to an oil bath to obtain a positive electrode active solution.

[0048] In this embodiment, in the step S11, the mass ratio of molybdenum powder, sulfur powder, conductive agent, binder and organic solvent is 1:10:10:5-15:100, so that the conductive property of the lithium-sulfur battery positive electrode material has excellent conductive property, inhibits the polysulfide shuttle effect of the lithium-sulfur battery, and can also improve the overall flexibility of the lithium-sulfur battery positive electrode material.

[0049] In the present embodiment, in the step S11, the conductive agent is one or more of carbon nanotubes (CNT) and Ketjen black (KB), the binder is polyvinylidene fluoride (PVDF), and the organic solvent is N,N-dimethylformamide (DMF). After Mo, S, KB and CNT are fully ground, the catalyst molybdenum not only has excellent conductive properties, but also has excellent binding and conversion capabilities for polysulfides. The zero-dimensional conductive material KB will adhere to the surface of the CNT to form a short-range conductive path, which greatly increases the conductivity of the material. The high adhesion of PVDF is utilized to perform phase transformation with a commercial PP diaphragm as the substrate, so that the positive electrode active coating is tightly bonded to the PP diaphragm to avoid swelling when encountering an electrolyte, while greatly increasing the overall flexibility.

[0050] In this embodiment, in step S12, the oil bath temperature is 60° C., the oil bath time is 6 h to 12 h, and the stirring speed is 100 rpm to 400 rpm, so that the positive electrode active liquid forms a uniform and stable solution.

[0051] Second, as Figure 3 As shown, the embodiment of the present application also provides a lithium-sulfur battery positive electrode material, which is prepared by the above-mentioned preparation method.

[0052] In this embodiment, the positive electrode material of the lithium-sulfur battery includes a battery separator and a positive electrode active coating coated on the battery separator, wherein the positive electrode active coating includes Mo, S, a conductive agent, a binder and an organic solvent, specifically, the conductive agent is KB and CNT, the binder is polyvinylidene fluoride (PVDF), and the organic solvent is N,N-dimethylformamide (DMF).

[0053] In a third aspect, an embodiment of the present application further provides a lithium-sulfur battery including a negative electrode material, a positive electrode material and an electrolyte, wherein the positive electrode material is a lithium-sulfur battery positive electrode material prepared by the above-mentioned preparation method or is the above-mentioned lithium-sulfur battery positive electrode material.

[0054] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0055] Example 1

[0056] This embodiment provides a method for preparing a positive electrode material for a lithium-sulfur battery, comprising the following steps:

[0057] After molybdenum powder, CNT, KB and sublimed sulfur of different masses are fully ground, DMF solvent with a mass ratio of 42 is added, and after sufficient mixing, PVDF with a mass ratio of 5 is added to form a suspension; then the above suspension is placed in an oil bath pot capable of magnetic stirring, heated to 80°C, and stirred overnight to obtain a positive electrode active liquid; a battery separator is laid on a glass plate, and then the positive electrode active liquid is coated on a PP separator, and an automatic coating machine is used to scrape the film to form a liquid film with a thickness of 200μm. After scraping the film, a water bath is immediately performed, wherein the solid phase conversion temperature is 20°C to 50°C, and the solid phase conversion time is 6h; the battery separator with the positive electrode active coating is separated from the glass plate, dried at room temperature for 12h, and then vacuum dried at 60°C for 12h to obtain a lithium-sulfur battery positive electrode material (Mo / C-CNT@PVDF / / PP), and finally cut into 19mm circular electrode sheets for subsequent experiments and characterization.

[0058] Comparative Example 1

[0059] The difference from Example 1 is that: after molybdenum powder, CNT, KB and sublimed sulfur of different masses are fully ground, a DMF solvent with a mass ratio of 42 is added, and after sufficient mixing, PVDF with a mass ratio of 5 is added to form a suspension; then the above suspension is placed in an oil bath pot capable of magnetic stirring, the temperature is raised to 80°C, and stirred overnight to obtain a positive electrode active liquid; the positive electrode active liquid is coated on a glass plate, and an automatic coating machine is used to scrape the film to form a liquid film with a thickness of 200 μm, and a water bath is immediately performed after scraping, wherein the solid phase conversion temperature is 20°C to 50°C, and the solid phase conversion time is 6h; the battery separator formed with the positive electrode active coating is separated from the glass plate, and after drying at room temperature for 12h, it is vacuum dried at 60°C for 12h to obtain a lithium-sulfur battery positive electrode material (Mo / C-CNT@PVDF), and finally it is cut into 19mm circular electrode sheets for subsequent experiments and characterization.

[0060] Comparative Example 2

[0061] The difference from Example 1 is that: after CNT, KB and sublimed sulfur of different masses are fully ground, DMF solvent with a mass ratio of 42 is added, and after sufficient mixing, PVDF with a mass ratio of 5 is added to form a suspension; then the above suspension is placed in an oil bath pot capable of magnetic stirring, heated to 80°C, and stirred overnight to obtain a positive electrode active liquid; the positive electrode active liquid is coated on a PP diaphragm, and an automatic coating machine is used to scrape the film to form a liquid film with a thickness of 200 μm, and a water bath is immediately performed after scraping, wherein the solid phase conversion temperature is 20°C to 50°C, and the solid phase conversion time is 6h; the battery diaphragm with a positive electrode active coating is separated from the glass plate, dried at room temperature for 12h, and then vacuum dried at 60°C for 12h to obtain a lithium-sulfur battery positive electrode material (C-CNT@PVDF / / PP), and finally cut into 19mm circular electrode sheets for subsequent experiments and characterization.

[0062] Indicator testing

[0063] Swelling test of sulfur battery positive electrode materials: The Mo / C-CNT@PVDF / / PP circular electrode sheet in Example 1 and the Mo / C-CNT@PVDF circular electrode sheet in Comparative Example 1 were immersed in the electrolyte and then taken out, and the diameters of the Mo / C-CNT@PVDF / / PP circular electrode sheet and the Mo / C-CNT@PVDF circular electrode sheet after immersion were measured.

[0064] Tensile test: According to GB228, tensile tests were performed on Mo / C-CNT@PVDF / / PP in Example 1, Mo / C-CNT@PVDF in Comparative Example 1, and C-CNT@PVDF / / PP in Comparative Example 2.

[0065] X-ray diffraction test: X-ray diffraction test was performed on Mo / C-CNT@PVDF / / PP in Example 1, Mo / C-CNT@PVDF in Comparative Example 1, and C-CNT@PVDF / / PP in Comparative Example 2 according to GB228.

[0066] Lithium-sulfur battery assembly: The Mo / C-CNT@PVDF / / PP circular electrode sheet in Example 1, the Mo / C-CNT@PVDF circular electrode sheet in Comparative Example 1, and the C-CNT@PVDF / / PP circular electrode sheet in Comparative Example 2 were used as the positive electrode, the metal lithium sheet was used as the negative electrode, 40 μL of organic electrolyte was added, and the electrochemical performance was tested.

[0067] XPS characterization: XPS characterization of Mo / C-CNT@PVDF / / PP in Example 1 was performed according to GB228.

[0068] Depend on Figure 3 It can be seen that the original diameters of the Mo / C-CNT@PVDF / / PP circular electrode sheet in Example 1 and the Mo / C-CNT@PVDF circular electrode sheet in Comparative Example 1 are both 19 mm, but after being soaked in the electrolyte, the Mo / C-CNT@PVDF circular electrode sheet swells and its diameter increases to 20 mm, while the diameter of the Mo / C-CNT@PVDF / / PP circular electrode sheet in Example 1 is still 19 mm, which fully demonstrates that the positive electrode active coating and the battery separator are integrally formed, which can not only prevent the positive electrode active coating from swelling when encountering the electrolyte, but also inhibit the polysulfide shuttle effect of lithium-sulfur batteries.

[0069] Figure 4The tensile strength test results of the lithium-sulfur battery positive electrode materials in Example 1, Comparative Examples 1 and 3 show that the greater the tensile force required for the lithium-sulfur battery positive electrode material to break, the better the flexibility of the lithium-sulfur battery positive electrode material. From the test results, it can be seen that the Mo / C-CNT@PVDF functional layer broke when it was deformed to 15% of its original length. Thanks to the extremely high flexibility of PP, after combining the functional layer with PP, the deformation of Mo / C-CNT@PVDF / / PP and C-CNT@PVDF / / PP reached 120%, and the flexibility was greatly improved.

[0070] Depend on Figure 5 It can be seen that the X-ray diffraction test of the positive electrode active coating of Mo / C-CNT@PVDF / / PP and C-CNT@PVDF / / PP shows that the positive electrode active coatings of the two lithium-sulfur battery positive electrode materials have two sharp and obvious diffraction peaks at 20.2° and 26.2°, which are the characteristic peaks of PVDF and CNT, respectively. In addition, Mo / C-CNT@PVDF / / PP also has obvious diffraction peaks at 40.5°, 58.6° and 73.7°, which correspond to the (110) crystal plane, (200) crystal plane and (211) crystal plane in the standard peak spectrum of Mo (PDF#42-1120), respectively, indicating that the catalyst Mo element is successfully doped into the positive electrode active coating of Mo / C-CNT@PVDF / / PP.

[0071] Depend on Figure 6 It can be seen that Figure 6 (a) is the XPS spectrum of Li 1s, which can be divided into two characteristic peaks, located at 55.7 and 56.7 eV, respectively, attributed to Li-F (LiFSI in the electrolyte and the adsorption of F on Li) and Li-S bonds. Figure 6 (b) is the XPS spectrum of the F1s orbital. Before and after charging and discharging, in addition to the characteristic peak of -CF2 (687.9eV) of PVDF, there are two more characteristic peaks of Li-F (685.6eV) and -CF3 (689.26eV), which are attributed to the composition of the electrolyte. Figure 6 (c) is the XPS analysis of Mo element. It can be clearly seen in the figure that the characteristic peaks of Mo-O bond appear at 236.05 and 232.7 eV, which may be the result of Mo being oxidized in the air. x There is also an electrocatalytic effect on the conversion reaction of polysulfides. At the same time, Mo-Mo characteristic peaks were detected at 229.8eV and 228.4eV. After 200 cycles of the battery, the characteristic peaks in the Mo 3d orbital will shift to a certain extent. This may be the result of Mo polar adsorption of polysulfides, confirming the polar adsorption ability of Mo metal on polysulfides.

[0072] Table 1 Li corresponding to two integrated flexible cathodes + Diffusion coefficient

[0073]

[0074] Table 2 Electrochemical impedance of two different batteries

[0075]

[0076] It can be seen from Table 1 that the apparent Li + The diffusion coefficient is significantly larger than that of C-CNT@PVDF / / PP, indicating that Mo doping can accelerate the Li + The transfer rate within the material. As shown in Table 2, the charge transfer resistance of Mo / C-CNT@PVDF / / PP is 30.7Ω, which is significantly lower than that of Mo / C-CNT@PVDF (286Ω). It is speculated that this is because the interface resistance between the positive electrode active coating and PP is very small, thereby accelerating the electrochemical reaction kinetics.

[0077] In summary, the catalyst molybdenum not only has excellent electrical conductivity, but also has excellent binding and conversion capabilities for polysulfides. At the same time, the doped Ketjen black and Mo adhere to the CNT surface to form a short-range conductive path, thereby preparing a functional layer material with stronger conductivity. In addition, using the commercial PP film as the base for phase transformation, the high viscosity of PVDF is used to tightly adhere the functional layer to the PP film, which not only limits the swelling problem of the functional layer when encountering the electrolyte, but also greatly reduces the interface resistance between the functional layer and PP. At the same time, the tensile test shows that the composite of the functional layer and PP gives the material higher overall flexibility.

[0078] In the description of the present application, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.

[0079] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0080] In this application, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, an electrical connection, or communication with each other; it can be a direct connection, or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0081] In the present application, the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0082] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A method for preparing a positive electrode material for a lithium-sulfur battery, characterized in that: The following steps are involved: Step S1: mixing molybdenum powder, sulfur powder, conductive agent, binder and organic solvent in proportion to obtain a positive electrode active solution; Step S2: coating the positive electrode active solution in step S1 on the battery separator, and obtaining the positive electrode material of the lithium-sulfur battery after drying.

2. The method for preparing a positive electrode material for a lithium-sulfur battery according to claim 1, characterized in that: The step S2 specifically includes: Step S21: laying a battery separator on a glass plate, coating the positive electrode active solution in step S1 on the battery separator, and then immersing it in water to perform a solid phase conversion of the positive electrode active coating; Step S22: Separate the battery separator with the positive electrode active coating formed in step S21 from the glass plate, dry it at room temperature for 12 hours, and then vacuum dry it for 12 hours to obtain a lithium-sulfur battery positive electrode material, wherein the vacuum drying temperature is 40°C to 80°C.

3. The method for preparing a positive electrode material for a lithium-sulfur battery according to claim 2, characterized in that: In the step S22, the solid phase conversion temperature is 20°C to 50°C, and the solid phase conversion time is 4h to 12h.

4. The method for preparing a positive electrode material for a lithium-sulfur battery according to claim 1, characterized in that: In step S2, the battery separator is a polyethylene, polypropylene or polyimide separator.

5. The method for preparing a positive electrode material for a lithium-sulfur battery according to claim 1, characterized in that: The step S1 specifically includes: Step S11: Grind the molybdenum powder, sulfur powder and conductive agent, add an organic solvent to dissolve them, and after they are fully dissolved, add a binder and mix to form a suspension. Step S12: The suspension in step S11 is subjected to an oil bath to obtain a positive electrode active solution.

6. The method for preparing a positive electrode material for a lithium-sulfur battery according to claim 5, characterized in that: In the step S11, the mass ratio of molybdenum powder, sulfur powder, conductive agent, binder and organic solvent is 1:10:10:5-15:

100.

7. The method for preparing a positive electrode material for a lithium-sulfur battery according to claim 5, characterized in that: In the step S11, the conductive agent is one or more of carbon nanotubes and Ketjen black, the binder is polyvinylidene fluoride, and the organic solvent is N,N-dimethylformamide.

8. The method for preparing a positive electrode material for a lithium-sulfur battery according to claim 5, characterized in that: In the step S12, the oil bath temperature is 60°C, the oil bath time is 6 hours to 12 hours, and the stirring speed is 100 rpm to 400 rpm.

9. A positive electrode material for a lithium-sulfur battery, characterized in that: Prepared by the method according to any one of claims 1 to 8.

10. A lithium-sulfur battery, characterized in that: The invention comprises a negative electrode material, a positive electrode material and an electrolyte, wherein the positive electrode material is a lithium-sulfur battery positive electrode material prepared by the preparation method according to any one of claims 1 to 8 or is a lithium-sulfur battery positive electrode material according to claim 9.

Citation Information

Patent Citations

  • Positive electrode for lithium-air cell, preparation method and applications thereof

    CN103855406A

  • Flexible integrated thin-film electrode and method for preparing same

    CN106159197A

  • Flexible integrated thin-film lithium-sulfur or lithium ion battery cell, battery and preparation method thereof

    CN106252659A

  • High-activity positive electrode material catalyst for lithium-sulfur battery and preparation method of high-activity positive electrode material catalyst

    CN116764660A

Cited By

  • Preparation method, product and application of molybdenum nitride

    CN120736480A